THE IMPACT OF STUDENT PERCEPTIONS AND EXPECTATIONS ON STUDENT’S RESULTS: AN EMPIRICAL STUDY IN TEACHING THE INTRODUCTORY ACCOUNTING COURSE IN THE UNIVERSITY OF INDONESIA - Shauki, Elvia R.; Setyaningrum, Dyah (UI Scholars Hub, 2006)
This study analyses the impact o f student perceptions and expectations in teaching introductory accounting course, lecturer performance index (based on stu dent evaluation teaching score), pre-requisite results, high school origin and status o f the kigh school fo r the final results in taking the Introductory Accounting course taught in the second semester (Pengantar Akuntansi 2 or PA2) differentiated be tween student gender and major o f study. The aim behind this study is to get feed back in order to improve teaching in PA 2. With factor analysis, results indicate that there are five dominant factors that were retained fo r the purpose in determining student results o f PA2 (expectations, topics, preparation, ethical issues and level o f difficulties o f the course). To date, there has not been a study on the impact o f student perceptions and expectations to student ’s final results. Different level ofperception and expectations, results o f PA 1 and lecturer performance index significantly influence the results o f PA2. Male students who expect that the subject will be difficult have less perfor mance rather than those who expect the contrary. Male students who have high expectations that PA2 course will be useful and challenging have greater chance to pass the course successfully.